Analisis Volatilitas Harga Saham dan Return Abnormal: Perbandingan Sebelum dan Sesudah Pemilu - Ariani, Regita; Kristianto, Aloysius Hari (MARGIN ECO, 2024)
This research aims to examine events from one round of elections that occurred by analyzing the average of abnormal returns and stock price volatility before or after the event. In this research, researchers used the event study method. The period used in this research is 14 trading days, each of which is 7 days before and 7 days after the event occurs. The focus of this research is on the IHSG on the Stock Exchange market. Data were analyzed using descriptive statistical techniques and statistical difference tests. Meanwhile, hypothesis testing uses the one sample t test and the pared sample t test. The results of the one sample t test show that there is a significant abnormal return after the announcement of one round of election events, meanwhile the results of the average abnormal return test that researchers have tested show that there is a significant difference in abnormal returns (AAR) before and after the event, however. The market responded positively to the one-round election event in Indonesia. Meanwhile, the results of the cumulative average abnormal return (CAAR) test that researchers have tested show that there is no significant difference in the cumulative average abnormal return (CAAR) before and after the one-round election event in Indonesia.